2009
DOI: 10.1007/s10342-009-0267-5
|View full text |Cite
|
Sign up to set email alerts
|

Testing prescribed fire as a tool to promote Scots pine Pinus sylvestris regeneration

Abstract: Techniques for encouraging natural tree regeneration are of increasing interest to managers of Scots pine Pinus sylvestris forests. We tested prescribed Wre at a management scale, with deer present or excluded, as a means of increasing rates of Scots pine forest expansion on heathland. At a semi-natural pinewood in Scotland, ten experimental blocks were established, within range of pine seed-fall. Each block comprised four, 100 m 2 plots. Two plots at each site were burnt and two fenced, allowing the eVects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 61 publications
2
32
2
Order By: Relevance
“…This resulted in few seedlings being established and hence reduced the power of the study to measure treatment effects on pine seedling recruitment. The estimated detection rate of small seedlings would have allowed measurement of treatment differences had seed-fall been higher, as was the case in the related study of Hancock et al (2009). Despite this, some supporting evidence for cattle impacts promoting new pine seedling establishment came from the within-forest plot, where seed-fall will have been much higher.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This resulted in few seedlings being established and hence reduced the power of the study to measure treatment effects on pine seedling recruitment. The estimated detection rate of small seedlings would have allowed measurement of treatment differences had seed-fall been higher, as was the case in the related study of Hancock et al (2009). Despite this, some supporting evidence for cattle impacts promoting new pine seedling establishment came from the within-forest plot, where seed-fall will have been much higher.…”
Section: Discussionmentioning
confidence: 87%
“…This might give impacts that were not only more pronounced but also longer-lasting, allowing more seasons of seed-fall to contribute to pine seedling recruitment. However, managers should also carefully compare the potential of management using cattle, against other approaches, like prescribed fire, well supported as a tool for promoting Scots pine regeneration (Hancock et al 2009). Such approaches may have cost and biodiversity advantages, depending on site constraints and objectives.…”
Section: Conclusion: Management Implications and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the implementation of empirical results to the model will increase the potential of its practical application, especially in prescribed burning scenario. The following notion was also confirmed by empirical enhancement of Scots pine regeneration in Scotland (Hancock et al, 2009). …”
Section: Introductionmentioning
confidence: 49%
“…Through simulations, we demonstrated that the use of prescribed burning is much more effective than the removal of spruce. It has been confirmed empirically that prescribed burning enhances the regeneration of Scots pine in Scotland (Hancock et al 2009). Linder et al (1997) suggested that management plans for forest reserves should include management practices that maintain or mimic the natural disturbance regimes in a certain way.…”
Section: Discussionmentioning
confidence: 89%